RISK FACTORS OF EROSIVE ULCER LESION OF STOMACH AND DUODENUM IN THOSE SUFFERING FROM SEVERE THERMAL INJURY - D. O. Vagner; I. V. Shlyk; V. N. Yurina (Вестник анестезиологии и реаниматологии, 2018)
The value of changes in the acidogenic function of stomach as well as blood circulation disorders in the genesis of erosive ulcer lesions of gastrointestinal tract were evaluated in those suffering from severe thermal injury. The changes in the rates reflecting the blood circulation state (stroke volume, cardiac index, global end-diastolic volume, index of general peripheral vascular resistance) were monitored during the early period of the burn injury. The acidogenic function was tested with the help of endoscopic pH-metry in 24 ± 4 hours and on the 7th and 14th days from the moment of burn injury. It was found out that erosion and acute ulcers complicated by hemorrhage occurred in 12% of those suffering from severe thermal injury in the acute period of the burn disease. And all of them manifested severe blood circulation disorders during the burn shock period despite the anti-shock therapy. At the same stage of treatment hyperacidity occurred in not more than 7-14% of those severely burned, and the major part of patients manifested hypoacidity and unacidity. Changes association evaluation proved that in case of ischemia the protection factors of mucous coat were expressly inhibited and the minimum quantity of chlorohydric acid was enough to damage the mucous coat. The obtained results allowed justifying the pathogenic approach to prevention of erosive ulcer lesion of the mucous coat of the gastrointestinal tract in the patients with burn shock, which is to include first of all the adequate management of the shock, fastest restoration of microcirculation and effective anti-secretion therapy providing unacidity state.